Symptoms of Oesophageal Affection in Children With Scleroderma According to Mano-Impedancemetry: A Case Series - Marina Ju. Stepanyan; Elena V. Komarova; Nikolay N. Murashkin; Ekaterina I. Alexeeva (Union of pediatricians of Russia, 2019)
Background. Currently, scleroderma is a rather rare disease, including among children. Despite the growing interest of investigators in this pathology, the problem of diagnosing oesophageal affection in various forms of systemic sclerosis remains under-investigated since endoscopic data does not provide a complete picture of the oesophageal function. Currently, mano-impedancemetry (MIP) is the leading method in Europe for determining the oesophageal function, including in children with scleroderma; in the Russian Federation, it is used only in adults. Proper and timely evaluation of the oesophageal motility state will allow not only to expand our understanding of the disease pathogenesis but also to determine the efficacy of the initiated therapy and to give practice suggestions in terms of treatment tactics in the early stages of the disease. Our aim was to determine the possibilities of mano-impedancemetry for diagnosing oesophageal affection in juvenile scleroderma. Patients and Methods. The study included children with juvenile scleroderma taken to the department of rheumatology and dermatology from June to August 2016. To identify oesophageal function disorders, all patients underwent high-resolution manometry in combination with impedancemetry. Results. A decrease in the distal oesophageal contraction amplitude in more than 30% of "wet" swallows was found in 2 of 7 children with juvenile systemic scleroderma and in one of 6 children with juvenile focal scleroderma. All 13 patients had peristaltic waves in the distal oesophagus with an amplitude of <30 mm Hg. They had interrupted peristalsis, in which the peristaltic wave did not go through the entire length of the oesophagus; one of these patients showed a simultaneous contraction with an amplitude of <30 mm Hg. All children (n=13) showed a positive correlation (r= 0.021) between the systemic disease and impaired motility (р=0.021). Conclusion. Despite the clinical and laboratory methods for diagnosing scleroderma, the data of oesophageal mano-impedancemetry is an important criterion, primarily for the differential diagnosis of systemic and focal scleroderma, and assists in the early initiation of therapy for oesophageal motility disorders.Marina Ju. Stepanyan, Ekaterina I. Alexeeva, Elena V. Komarova confirmed the absence of a reportable conflict of interest.Ekaterina I. Alexeeva - receiving research grants from Pfizer, Roche, Centocor, Novartis.Nikolay N. Murashkin - receiving research funding from pharmaceutical companies Jansen, Eli Lilly. Receiving fees for scientific advice from Galderma, Pierre Fabre, Bayer, Astellas, Libriderm.